Insight Into the Role of Ceria on OMS-2 and OL Materials for Catalytic Degradation of Toluene - Yue, Lin; Hu, Minghua; Tian, Mingjiao; Liao, Xu; Xu, Zhihua; Shi, Ling; He, Chi (Frontiers in Environmental Chemistry, 2020)
Catalytic oxidation is one of the most efficient approaches for industrial volatile organic compounds (VOCs) elimination. MnOx-based catalysts have attracted much attention due to their remarkable low-temperature catalytic activity. Here, octahedral layered birnessite-type manganese oxide (OL-1) with layer spacing of 7 Å and cryptomelane type manganese oxide (OMS-2) with tunneled pore diameter of 4.6 × 4.6 Å were synthesized by a reflux method. Following this, Ce-doped OL-1 and OMS-2 were further prepared by an impregnation method with target to improve catalytic performance in toluene oxidation. Results reveal that the OMS-2 material exhibits the best catalytic activity with 90% of toluene decomposed at 224 °C owing to the presence of a large quantity of active lattice oxygen species. Interestingly, the introduction of Ce leads to the formation of large amounts of acidic sites, which limit the oxidation process and enhance the yield of benzoic acid by-product. The findings in the present work are meaningful for deepening our understanding of the role of ceria on metal oxide catalysts and helping us to design effective catalysts for VOC destruction.